Neurodevelopmental disorders in children exposed in utero to synthetic progestins: analysis from the national cohort of the Hhorages Association*. (4th March 2019) - Soyer-Gobillard, Marie-Odile; Gaspari, Laura; Courtet, Philippe; Puillandre, Mauricette; Paris, Françoise; Sultan, Charles
Abstract: The medical and scientific communities have not yet fully acknowledged the undesirable effects of the synthetic hormones that have been administered to pregnant women for decades. The somatic effects of in utero exposure to diethylstilbestrol (DES), such as genital malformations, infertility, and cancer, have long been recognized but this has not been the case concerning psychiatric disorders. The progestins used in contraception and hormone replacement therapy are known to affect the adult brain, but no data exist on their effects due to in utero exposure of children. The Hhorages Association, a national patient support group, has assembled a cohort of 1200 women who took synthetic hormones during pregnancy. These women had a combined 1934 children. We obtained full questionnaire responses from 46 women treated with progestins only – and not an estrogenic cocktail – who gave birth to 115 children. Three groups were observed: Group 1 ( n = 18): firstborn unexposed children, Group 2 ( n = 62): children exposed in utero to synthetic progestins, and Group 3 ( n = 35): children born after a previous pregnancy treated with progestins. No psychiatric disorders were reported in Group 1 and the incidence of psychiatric disorders was drastically elevated in Group 2. Our work shows a striking increase in psychiatric disorders among children exposed in utero to progestins and strongly suggests that prenatal exposure is associated with a high risk of psychiatric disorders in adolescence and adulthood, whether accompanied or not by disorders of sex development.